Enhancing patient activation: a controlled implementation study of an interprofessional evidence-based counseling program for complementary and integrative healthcare in cancer patients ('CCC-Integrativ') - Valentini, Jan; Froehlich, Daniela; Roesel, Inka; Stolz, Regina; Mahler, Cornelia; Martus, Peter; Klafke, Nadja; Horneber, Markus; Witte, Claudia; Kramer, Klaus; Greil, Christine; Grün, Barbara; et al. (Frontiers of medicine, 2024)
Complementary and integrative healthcare (CIH) is increasingly recognized as a valuable approach to empowering and activating cancer patients. Studies have shown that higher patient activation is positively associated with improved health outcomes and reduced healthcare costs. The CCC-Integrativ study aimed to assess the implementation of an evidence-based counseling service on CIH at four Comprehensive Cancer Centers (CCC) in Germany. In this controlled implementation study, the patient-level intervention included three CIH consultations within a 3-month period delivered by interprofessional teams of physicians and nurses. The primary endpoint was patient activation using the PAM-13 at baseline (T1) and post-intervention (T2), and compared between control (CO, receiving routine care) and the intervention group (IG) using an analysis of covariance. Missing data were handled with multiple imputations. Maintenance effects at 6-month follow-up (T3) were investigated using a linear mixed model. A total of n = 1128 oncology patients (CO = 443, IG = 685) with diverse tumor entities and cancer stages were included in the study. The overall mean baseline PAM-13 score was 69.74 (SD = 14.24) (n = 959 (85.0%)). A statistically significant between-group difference in post-intervention PAM-13 scores was observed (Fgroup(1, 1866.82) = 8.634, P = 0.003), with an adjusted mean difference of 2.22 PAM-points. Age, gender, tumor entity, disease stage, or CCC study site did not significantly predict post-treatment PAM-13 scores. The maintenance effect of the intervention was not statistically significant (FtimeXgroup(1, 3316.04) = 2.337, P = 0.096). Individually tailored counseling on CIH, offered by specifically trained, interprofessional teams, significantly improved patient activation. Given the established positive effects of higher patient activation, the implementation of such a program at cancer centers may yield beneficial outcomes for both patients and the healthcare system.